An overview of sports-mediated brain injuries and their management approaches: a narrative review - Parul Grover; Hadi Nobari; Monika Bhardwaj; Lovekesh Mehta; Garima Kapoor; Pooja A. Chawla; Luca Paolo Ardigò (Termedia Publishing House, 2024)
Purpose The objective of the present study was to provide an update on the 16 sports with the highest incidence of brain injuries. Thereafter, its diagnosis, treatment, and management strategies are discussed. Methods The manuscript addresses the brain-related injuries individually in each of the 16 sports with the highest incidence. To simplify the reading, the mentioned 16 sports are sorted alphabetically. A subpart mentioning the management of brainrelated sports injuries, including pharmacological management, is also included in the manuscript. Results The incidence of sports-mediated brain injuries within hospital-based studies ranged between 3.5 and 31.5 per 100,000. One community-based study using multiple case ascertainment sources identified a higher incidence of 170 per 100,000. Brain injuries due to sports total 1.2-30.3% of all TBIs (traumatic brain injuries). Men have a higher prevalence than women (75.6% vs. 66.1%), and adolescents and young adults had the highest incidence of sports-mediated brain injuries. Almost 50% of head injuries reported during the practice of sports or recreational activities occur in bicycling, skateboarding, or skating incidents. More than 775,000 children, aged 14 and younger, are treated yearly in hospital emergency rooms for sports-related injuries. Conclusions Brain injuries are common in sports and difficult to manage, but athlete health and injury prevention should be the priority. Preventive measures should be stricter in sports with a higher incidence of brain injury. As for treatment, a comprehensive approach should be adopted.